2020
DOI: 10.1055/s-0040-1709429
|View full text |Cite
|
Sign up to set email alerts
|

Revision Surgery of the Cleft Palate

Abstract: Cleft palate repairs often require secondary surgeries and/or revisions for a variety of reasons. The most common causes are symptomatic oronasal fistulas and velopharyngeal insufficiency. Complications from primary surgery, such as wound dehiscence, infection, and hematomas, contribute to the relatively high rate of revision surgery. Prevention of postoperative complications that may lead to fistula or velopharyngeal insufficiency is key, and many techniques have been described that have reportedly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…However, the focus with secondary palate repair is more functional, aiming to address either VPI or oronasal fistula. 26 Our subgroup analysis revealed that only 9.4% of those undergoing secondary palatoplasty were documented to address VPI. It is important to note that this percentage is likely an underestimation, as only 47% of patients in the VPI cohort had an ICD 9 or ICD 10 code indicating VPI.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the focus with secondary palate repair is more functional, aiming to address either VPI or oronasal fistula. 26 Our subgroup analysis revealed that only 9.4% of those undergoing secondary palatoplasty were documented to address VPI. It is important to note that this percentage is likely an underestimation, as only 47% of patients in the VPI cohort had an ICD 9 or ICD 10 code indicating VPI.…”
Section: Discussionmentioning
confidence: 79%
“…Patients undergoing palate repair may also require a secondary revision operation. However, the focus with secondary palate repair is more functional, aiming to address either VPI or oronasal fistula 26 . Our subgroup analysis revealed that only 9.4% of those undergoing secondary palatoplasty were documented to address VPI.…”
Section: Discussionmentioning
confidence: 87%
“… Decision tree on surgical techniques for palatal fistulae (Reprinted with permission from [ 17 ]. Copyright 2020, Shirley Hu.)…”
Section: Figurementioning
confidence: 99%
“…The choice of the surgical technique is mainly made based on the location and size [ 14 , 15 , 16 ]. Hu et al describe a very detailed decision tree ( Figure 2 ) based on the Pittsburg classification ( Figure 1 ) [ 17 ]. The timing and the choice of the surgical technique allow an increase in the success rate in closing the palatal fistulae [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palatal wound healing happened after cleft palate repair and trauma and tumor excision ( Majid, 2008 ; Sahoo et al, 2016 ; Alonso et al, 2019 ). Poor palatal wound healing could lead to oronasal fistula (ONF), resulting from extensive tension, infection, or hematoma ( Hu and Rousso Joseph, 2020 ; Pollard et al, 2020 ). Oronasal fistula (ONF) was a common complication after cleft palate repair, which manifested as abnormal communication between oral and nasal cavities ranging from the alveolar process to the uvula ( Honnebier et al, 2000 ; Mahajan et al, 2018 ; Alonso et al, 2019 ; Pollard et al, 2020 ), which could cause food reflux, unclear pronunciation and impaired velopharyngeal function, which affected the patient’s quality of life ( Mahajan et al, 2018 ; Garg et al, 2019 ; Huang et al, 2023b ).…”
Section: Introductionmentioning
confidence: 99%